Hello all~ I'm doing a problem where Integration by parts is used and i have reached a part where i'm stumped.
The problem is
I've let u = ln(2x+1) dv = dx
du = 2 / (2x+1)dx v = x
xln(2x+1) - integrate (2x)/(2x + 1) dx
I'm having problems integrating (2x) / (2x + 1) dx. It seems something so simple but when I tried it out a couple times, it simply doesn't match up to my teachers answer. He was able to make the above into
Integrate 1 - (1/(2x + 1)) which I can do fairly easily by using substitution. Any help is appreciated.